2014
DOI: 10.1016/j.canlet.2013.10.010
|View full text |Cite
|
Sign up to set email alerts
|

One mouse, one patient paradigm: New avatars of personalized cancer therapy

Abstract: Over the last few decades, study of cancer in mouse models has gained popularity. Sophisticated genetic manipulation technologies and commercialization of these murine systems have made it possible to generate mice to study human disease. Given the large socio-economic burden of cancer, both on academic research and the health care industry, there is a need for in vivo animal cancer models that can provide a rationale that is translatable to the clinic. Such a bench-to-bedside transition will facilitate a long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
214
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 253 publications
(224 citation statements)
references
References 95 publications
2
214
1
4
Order By: Relevance
“…Given the strictly limited accessibility to clinical test of c-Met inhibitors, we alternatively resorted to patient-derived xenograft (PDX) models, which faithfully recapitulate tumor heterogeneity and histologic characteristics of primary tumors, to mimic the clinical settings (42)(43)(44).…”
Section: C-myc Directs Clinical Decision-making In Met-oriented Clinimentioning
confidence: 99%
“…Given the strictly limited accessibility to clinical test of c-Met inhibitors, we alternatively resorted to patient-derived xenograft (PDX) models, which faithfully recapitulate tumor heterogeneity and histologic characteristics of primary tumors, to mimic the clinical settings (42)(43)(44).…”
Section: C-myc Directs Clinical Decision-making In Met-oriented Clinimentioning
confidence: 99%
“…A plethora of evidence, including high fidelity in mutational status, transcriptome, histology, polymorphism and copy number variation, also supports the notion that PDTX models remarkably resemble the pathophysiology of human tumors more closely than traditional Cancer-derived xenograft (CDX) models [16]. This convincing data suggests PDTX are informative models to study clonal evolution along serial passages, at the rates reported in primary tumors [17][18][19][20][21][22][23][24]. Notably, PDTX grow within a rich host environment and the relationship between human tumors and mouse host elements have been proven to be critical for the successful engraftment, growth and response to therapy [25].…”
Section: Introductionmentioning
confidence: 66%
“…Thus, drugs that impair leukemic engraftment may affect outcomes, a possibility that must ultimately be tested in clinical trials. Patient-derived tissues that have been serially propagated as xenografts (distinct from primary patient samples) have been used previously by the Pediatric Preclinical Testing Program (29) and others (30) to test a panel of therapeutic agents against a limited number of individual tumors. Although effective in screening potential new drugs, this approach does not capture interpatient tumor heterogeneity nor allow for identification of drug response biomarkers.…”
Section: Discussionmentioning
confidence: 99%